Translation of metaphors into Persian in the subtitling of American movies / Ahmad Iranmanesh - Iranmanesh, Ahmad (2014)
The topic of the present thesis is ‘Translation of Metaphors into Persian in the Subtitling of American Movies’. Here, the notion of ‘metaphor’ is restricted to orientational metaphors which are among the three basic types of metaphors presented by Lakoff and Johnson (1980) in their Contemporary Theory of Metaphor (CTM). On the other hand, the term ‘subtitling’ is bound to interlingual subtitling which is defined by Karamitroglou (2000) as the translation of the spoken (or written) source text of an audiovisual product into a written target text which is added into the images of the original product, usually at the bottom of the screen. Therefore, this is an investigation about the interlingual subtitling of the English orientational metaphors in Persian. The required data for this study has been extracted from ten original American action movies. The researcher has extracted the English orientational metaphors from the movies under this study based on the definition provided for this particular type of metaphor in the CTM. In the next step, the English metaphors are interpreted based on the basic patterns of orientational metaphors by Lakoff and Johnson (1980). The background model of this thesis is the cognitive model of Al-Hasnawi (2007) for the translation of the SL metaphor to the TL. The collected orientational metaphors are grouped under three schemes, which are presented in Al-Hasnawi’s model, to classify them as universal and culture-specific and to translate them into Persian by the strategies which are presented for each scheme in this model. After the discussion of findings, the researcher noticed that a considerable number of the extracted data belonged to a group which was not accounted for in the model of Al-Hasnawi; therefore, he suggested another scheme and its relevant strategy for inclusion among the ones presented by A-Hasnawi. The findings of this thesis determine the basic patterns of mapping conditions for the orientational metaphors under this study based on the CTM. In the meantime, it is clearly shown that the three schemes and their relevant strategies presented by Al-Hasnawi (2007) are effective in the classification of the extracted English metaphors and their translation to Persian. Moreover, the researcher’s recommended scheme and its relevant strategy for the translation of metaphors from English to Persian prove to be quite applicable in classifying and subtitling the collected orientational metaphors in this thesis.